Does Digital Financial Inclusion in Sharia Commercial Banks Drive Economic Transformation in Madura? - Khasanah, Riskiyatul; Azizah, Nur (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2023)
The urgency of financial inclusion has been widely recognized and has even become one of the focuses of governments in several countries in the world, including Indonesia. In the era of increasingly rapid digital acceleration due to the pandemic, financial inclusion by banks that focus on digitalization takes a significant role in realizing a better economic transformation through digital financial services, Laku Pandai, digital account ownership, and other financing facilities. Sharia Commercial Banks are still the driving force for financial services in various regions in Indonesia, including Madura, this is because banking has a scope that is more accessible to the public and fulfills the religious value of the Madurese community. The purpose of this study is to determine whether Sharia Commercial Banks have been able to encourage economic transformation in Madura inclusively in the digitalization era. This study uses quantitative research methods with multiple linear regression analysis (Ordinary Least Square) with the help of EViews 9.0 software. The result of the study found that the contribution of financial inclusion made by Sharia Commercial Banks was able to encourage economic transformation in Madura and Showed significant development.